21.4: Deposition Conditions and HRTEM Characterization of CAAC IGZO. Issue 1 (June 2015) - Lynch, David M.; Zhu, Bin; Levin, Barnaby D. A.; Muller, David A.; Ast, Dieter G.; Greene, Raymond G.; Thompson, Michael O.
Abstract : Crystallinity and texture of c‐axis aligned crystal indium gallium zinc oxide (CAAC IGZO) films deposited by RF reactive sputtering were studied and characterized over a range of deposition conditions. The characteristic CAAC (009) peak at 2θ=30° was observed by X‐ray diffraction, and nanocrystalline domain texture was determined using a general area detector diffraction system (GADDS). Highly ordered CAAC films were obtained near the InGaZnO4 composition at a substrate temperature of 310°C and in 10% O2 . High‐resolution transmission electron microscopy (HRTEM) confirmed the formation of CAAC showing 2‐3 nm domains aligned over 15 nm x 15 nm fields of view. Cross‐section HRTEM of the CAAC/substrate interface shows formation of an initially disordered IGZO layer prior to CAAC formation, suggesting a nucleation mechanism similar to ZnO thin films.